PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL TERHADAP OBAT TRADISIONAL MINYAK KARO - Siti Fadilah; Maniar Nainggolan; Reh Bungana Beru Perangin-angin (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
Indonesia is a country with abundant biodiversity scattered in various regions, one of which is biodiversity spread in the Karo Regency area which can be used as a traditional medicine